Performance evaluation of newly developed fluorescence immunoassay-based interferon-gamma release assay for the diagnosis of latent tuberculosis infection in healthcare workers - Oh Joo Kweon; Yong Kwan Lim; Hye Ryoun Kim; Tae-Hyoung Kim; Mi-Kyung Lee (Journal of Microbiology, Immunology and Infection, 2022)
The ichroma™ IGRA-TB (Boditech Med Inc., Chuncheon, Republic of Korea) is an automated fluorescent immunoassay-based point-of-care interferon-gamma release assay for detecting latent tuberculosis infection. We evaluated this assay with 408 health care workers, and demonstrated its acceptable performances comparing to QuantiFERON-TB Gold-Plus (QFT-Plus; Qiagen, Germantown, MD).